Live, Love And Laugh - Chawla, Majit Sargam; Raj, Yogi Amrit (New Delhi Srishti, 2019)
Are you tired of putting in endless efforts, with no goal or results in sight? Do you find it difficult to cope with a hectic lifestyle that drains you of all energy? Has the race to perform exceptionally worn you out completely? Love, laughter and a happily ever after have been some of the goals that we rush to achieve throughout our lives. But in trying to live, we forget to love; in trying so hard to be content, we forget to laugh. Our mind holds the key to some of the best gifts life has to offer, and this book helps us unlock them. Live, love and laugh is a guide to applying the principles of yoga for understanding the human mind and character. The book is a coming together of the practice of yoga, along with the principles and Practice of the law of attraction, making it a spell-binding read.
Keywords: Human Mind And Character; Yoga